The Implementation of Islamic Religious Guidance Classes Among Mualaf During the COVID-19 Pandemic Season - Siti Marpuah; Kirin, Arwansyah; Saparudin, Intan Farhana; Ahmad, Shakila; Nordin, Shah Rul Anuar; Ubaidillah (Journal of Techno-Social, 2022)
The COVID-19 pandemic that has hit the whole world has a great impact on the teaching and learning system, including in the implementation of Islamic religious guidance among mualaf at MACMA Johore State. This study aims to see how Islamic religious guidance classes are implemented among mualaf at MACMA during the COVID-19 pandemic. This study uses qualitative methods through interviews, observations and document collection to answer the research questions. The results of the study show that during the COVID-19 pandemic season, the converts followed the Islamic religious guidance class through the Google Meet application that had been prepared by the instructor. While the problem faced by converts is the difficulty in handling Google Meet, in addition to that, their understanding of the subject presented by the instructor is also reduced.